Bromeliad flora of Oaxaca, Mexico: Richness and distribution - Espejo-Serna, Adolfo; López-Ferrari, Ana Rosa; Martínez-Correa, Nancy; Pulido-Esparza, Valeria Angélica (Instituto de Ecología, A.C., 2007)
The current knowledge of the bromeliad flora of the state of Oaxaca, Mexico is presented. Oaxaca is the Mexican state with the largest number of bromeliad species. Based on the study of 2,624 herbarium specimens corresponding to 1,643 collections, and a detailed bibliographic revision, we conclude that the currently known bromeliad flora for Oaxaca comprises 172 species and 15 genera. All Mexican species of the genera Bromelia, Fosterella, Greigia, Hohenbergiopsis, Racinaea, and Vriesea are represented in the state. Aechmea nudicaulis, Bromelia hemisphaerica, Catopsis nitida, C. oerstediana, C. wawranea, Pitcairnia schiedeana, P. tuerckheimii, Racinaea adscendens, Tillandsia balbisiana, T. belloensis, T. brachycaulos, T. compressa, T. dugesii, T. foliosa, T. flavobracteata, T. limbata, T. maritima, T. ortgiesiana, T. paucifolia, T. pseudobaileyi, T. rettigiana, T. utriculata, T. x marceloi, Werauhia pycnantha, and W. nutans are recorded for the first time from Oaxaca. Collections from 226 (of 570) municipalities and all 30 districts of the state were studied. Among the vegetation types occurring in Oaxaca, oak forest is the richest with 83 taxa, followed by tropical deciduous forest with 74, and cloud forest with 73 species. Species representation and distribution in Oaxaca are analyzed in detail. We also provide a comparison with bromeliad floras of the states of Chiapas, Guerrero, Puebla and Veracruz. The analysis of the species and collections by altitudinal intervals shows that the highest numbers of both ocurre between 1,500 and 2,000 m, with the number of species markedly decreasing above 2,500 m.